2012
DOI: 10.1177/1473325012450484
|View full text |Cite
|
Sign up to set email alerts
|

‘But they’re happening to you at the wrong time’: Exploring young adult women’s reflections on serious illness through photovoice

Abstract: Although serious illness is often associated with aging, many young adults are affected by various life-threatening and chronic illnesses, and thus have experiences that do not correspond to socio-cultural expectations for young adulthood. In this article, we describe a qualitative study exploring young adult women's experiences of serious illness. Ten participants diagnosed with a life-threatening or chronic illness in the previous three years participated in phenomenological interviews and photovoice project… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 27 publications
(41 reference statements)
1
14
0
Order By: Relevance
“…We report elsewhere our findings that relate young women's experiences to socio-cultural ideals regarding the life course (Burles & Thomas, 2012). In this article, we focus on the photographic component of the research and what it revealed about participants' embodied experiences, as well as their reflections on participation.…”
Section: Discussionmentioning
confidence: 99%
“…We report elsewhere our findings that relate young women's experiences to socio-cultural ideals regarding the life course (Burles & Thomas, 2012). In this article, we focus on the photographic component of the research and what it revealed about participants' embodied experiences, as well as their reflections on participation.…”
Section: Discussionmentioning
confidence: 99%
“…While many Photovoice studies are community-based and focused on health promotion, this approach has also been used to explore subjective understandings of lived experiences, particularly those that may be difficult to put into words such as experiences of life-threatening, chronic, or mental illnesses (Burles and Thomas 2014;Guillemin and Drew 2010;Thompson et al 2008). In addition, Photovoice has shown promise in previous research conducted with adolescents, young adults, and individuals with intellectual disabilities (Burles and Thomas 2012;Drew, Duncan, and Sawyer 2010;Jurkowski and Paul-Ward 2007). As such, we deemed Photovoice suitable for accessing lived experiences of young adults with FASD, prompting reflection by participants, and allowing for creativity in expression that goes beyond language.…”
Section: Methodsmentioning
confidence: 99%
“…Although the interview aimed to explore life with FASD, the condition was not always central in the discussion; specifically, the participant talked at length about the transition out of high school and into adulthood, and his efforts to navigate this challenging time of life. As such, FASD was observed to be one component of his multi-faceted life, rather than the dominant feature of his identity, which we discuss further elsewhere (Burles et al 2016b). During the interview, the participant was also asked about his advice for others with FASD and the general public.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature specifically investigating young women’s subjective experiences of breast cancer is sparse, and young women diagnosed during pregnancy have been occasionally involved in such studies. For example, one woman in Burles’ [14] study of young people with serious illnesses was diagnosed with BCDP, and one woman in Kirkman et al’s [15] study of young women with breast cancer was diagnosed early in her pregnancy. Further in-depth insight into the accounts of young women diagnosed during pregnancy is, therefore, badly needed.…”
Section: Introductionmentioning
confidence: 99%